International economics : analysis and issues - Staley, Charles E. (Englewood Cliffs, N.J. : Prentice-Hall, 1970)
The organizing principle for the book itself is to present the subject on the basis of what is done by international economists. It contains the concoction of models of international trade and finance, extending, revising, and replacing previous models; the study of patterns of trade and finance and; finally, there is comment on the policies followed by governments and suggestions about desirable alternative policies.
Includes bibliographical references and index.
ne 19/08/2019
Loans
Keywords: International economic relations